Cold shock combined with salicylic acid treatment alleviated postharvest chilling injury of wax apple by maintaining cell membrane and cell wall integrity - Liangyi Zhao; Xiangying Che; Ziling Qi; Yonghua Zheng; Peng Jin (Postharvest Biology and Technology, 2027)

Dopamine triggers TOR signaling cascade to drive biomass and astaxanthin hyperaccumulation in Haematococcus lacustris under coordinated salinity and gradient light stress - Shiyu Lin; Qingwei Wang; Raoqiong Che; Qingqing Li; Chunli Yu; Min Yang; Lifang Li; Penghua Gao; Ying Qi; Feiyan Huang; Xiang Wang; Yongteng Zhao; et al. (Bioresource Technology, 2026)

Numerical simulation on giant reed co-firing performance of circulating fluidized bed in thermal power plant to reduce carbon emission - Jiamiao Liu; Pengbo Zhao; Chenglong Yang; Qingwei Wang; Liujun Chang; Shi'en Liu; Chang'an Wang; Defu Che (Biomass and Bioenergy, 2026)

A potent protein vaccines OmpW induces strong protective immunity against Klebsiella pneumoniae in a mouse model - Ting Huang; Siyou Che; Hong Zhang; Wei Jiang; Danrui Hao; Zheng Lv; Yang Yuan; Yundong Zhang; Ruibin Yang; Linqiu Luo; Lufeng Dan; Yiwen Chu; et al. (Medical Microbiology and Immunology, 2026)

AuNPs-VS2-Mediated LSPR-SPR-Coupled optical fiber biosensor for sensitive and acid-stable detection of H. pylori - Hongxi Wang; Jiantao Zhang; Lingzhu Gou; Jiangbo Zhao; Tuanjie Che; Dekui Zhang; Liyun Ding (Analytica Chimica Acta, 2026)

Dynamics simulation on microstructural properties evolution of high-alkali coal slag in reducing conditions: The roles of alkali oxide, alkaline earth oxides, and iron oxide - Guowei Ma; Junyan Gu; Maoyun Luo; Chang’an Wang; Jiamiao Liu; Yonggang Zhao; Lin Zhao; Limin Wang; Wanzhu Wu; Hu Wang; Defu Che (Fuel, 2026)

Functional probiotic Ligilactobacillus agilis Z22 enhances gut–lung immune defense in chickens through TLR2/IL-10–JAK1/STAT3 signaling - Qiao Guo; Yingjie Wang; Jiahui Wu; Zhenghao Che; Shan Lv; Wenqing Zhao; Shiying Li; Jin Liu; Xiuli Peng (Food Bioscience, 2026)

Efficient vitrification of hazardous waste incineration fly ash and slag via the CaO-SiO2-Fe2O3 system - Yuyang Long; Zheyu Chen; Yuhe Song; Chen Liu; Jing Hou; Lei Che; Wangyang Tian; Weiwei Zhao; Bochao Dong; Dongsheng Shen; Foquan Gu (Environmental Research, 2026)

Corrigendum to “Hyperoside impairs mitochondrial respiration in chronic myeloid leukemia by promoting STUB1-mediated ubiquitination and degradation of NOX4” [Toxicology and Applied Pharmacology 511 (2026) 117795] - Hong Che; Bingjie Zhao; Wenjing Yi; Peijia Liu; Lian Hu (Toxicology and Applied Pharmacology, 2026)

Activation-optimized anti-CD3 valency control enables combinatorial discovery of multi-specific nanoantibodies for solid tumor immunotherapy - Long Zhu; Ya-Jing Ma; Jian-Kang Kang; Xiu-Hai Che; Dong-Kun Zhao; Yin-Yi Cai; Yao-Ru Yu; Song Shen; Jun Wang (Science Bulletin, 2026)

Concentration and depth-resolved analysis of transition metals in atmospheric particles: A combined approach using X-ray fluorescence and synchrotron radiation single-particle imaging - Yiliang Liu; Jiawei Zhou; Hanxiong Che; Difei Zhang; Pingping Wen; Yifan Zhao; Xin Du; Lingshuo Meng; Yan Han; Zhier Bao; Xin Qi; Xin Long; et al. (Journal of Environmental Sciences, 2026)

Maximizing economic and environmental benefits in China's rice farming with an adaptive deep learning framework - He Xu; Xinge Zhao; Xin Yang; Zihan Liu; Zhixuan Che; Jinrong Shen; Zelin Huang; Dan Xia; Yongqiu Xia (Field Crops Research, 2026)

Exposure to O3, NO2 and their oxidative potential in relation to decreased fecundability: The potential contribution of inflammatory hematological markers - Bingxue Wu; Zigao Zhao; Yan Zhang; Cai Kong; Yuyan Li; Yishi Jiang; Zhengyuan Xie; Xiangjing Song; Tao Wang; Yan Che (Environmental Research, 2026)

Interfacial engineering of MOF functionalized BN networks for preparation of polyurethane-based phase change composites with excellent thermal conductivity and thermal management properties - Chenxia Zhen; Yinghua Che; Enqi Chen; Jian Zhao; Yanlong Luo; Xiujuan Wang (Chemical Engineering Journal, 2026)

A gradient boosting-based machine learning framework for improving atmospheric visibility numerical prediction - Chen Han; Hong Wang; Ke Gui; Xutao Zhang; Wenjie Zhang; Yue Peng; Yang Zhao; Zhaodong Liu; Huizheng Che; Xiaoye Zhang (Atmospheric Research, 2026)

The CMA Chemistry–Weather Coupled Model and Its Operational Forecast of Fog–Haze and Sand/Dust Storms - Hong Wang; Xiaoye Zhang; Wenjie Zhang; Yue Peng; Ping Wang; Hongli Liu; Zhaorong Zhuang; Liping Huang; Weihong Tian; Yang Zhao; Ke Gui; Chen Han; et al. (Journal of Meteorological Research, 2026)

Continuous Diurnal–Nocturnal Observation of Atmospheric Aerosols: Mechanisms, Challenges, and the Prospects of AI Empowerment - Huizheng Che; Yu Zheng; Lei Li; Ke Gui; Hengheng Zhao; Junli Jin; Xiaochun Zhang; Xiang’ao Xia; Yupeng Wang; Zhiwei Xia; Yucong Miao; Yaqiang Wang; et al. (Journal of Meteorological Research, 2026)

Reduced irrigation and phosphorus redistribution optimizes common vetch–mediated soil metabolic and microbial shifts suppress potato late blight - Ting Che; Shan Sun; Yilei Zhou; Chenxi Wu; Tingting Sun; Kangji Gao; Feng Hu; Huixin Li; Huijuan Zhang; Peiyi Zhao; Li Xu (Agriculture, Ecosystems & Environment, 2026)

Study on the anti-inflammatory effects of active ingredients in Vespa velutina auraria Smith - Ming-Rong Li; Xiu-Qin Pang; Chao-He Liu; Wei Zhang; Heng Liu; Hai-Rong Zhao; Zhi-Bin Yang; Yan Wang; Yi-Hao Che; Huai Xiao (Natural Product Research, 2026)

Prenylated dihydrostilbenoid derivatives from the aerial parts of Glycyrrhiza uralensis and their potent antibacterial activity against drug-resistant clinical isolates - Yuxuan Zhong; Junfei Zhou; Shanwei Hu; Mengting Wang; Jingyu Liu; Jicong Du; Jin-Ao Duan; Hongkai Bi; Ming Zhao; Chun-Tao Che (Phytochemistry, 2026)

Characterization of the chemical constituents changes in Amomum tsao-ko during different storage periods using ultra-fast gas phase electronic nose and UHPLC-Q exactive HF-X - Mengmeng Hu; Shen Zhuang; Yi Zhao; Yanyun Che; Yunpeng Fan (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Two-phase thin film flow in the compressor’s clearance considering gaseous cavitation of refrigerant/oil based on a novel CFD approach - Jiachen Li; Hui Zhang; Yongxiang Guo; Tian Zhang; Zibo Zhao; Che Wang; Jianhua Wu (International Journal of Refrigeration, 2026)

Hyperoside impairs mitochondrial respiration in chronic myeloid leukemia by promoting STUB1-mediated ubiquitination and degradation of NOX4 - Hong Che; Bingjie Zhao; Wenjing Yi; Peijia Liu; Lian Hu (Toxicology and Applied Pharmacology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Distribution characteristics and potential microbial degradation mechanisms of microplastics in oyster aquaculture areas of southern China - Hui Zhao; Wenxue Che; Xiao Tan; Yuhan Shen; Yue Xu; Ying Man (Journal of Hazardous Materials, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

Insight into influencing factors and simulating models of migration, potential hazards, and analytic technology on microplastic in agricultural soil - Che Zhao; Xixi Lian; Yazhuo Wang; Ying Gu; Dong Liang (Journal of Environmental Sciences, 2026)

Al surface doping strategy enables manganese ion sieve to improve structure stability and adsorption capacity toward lithium extraction - Shibo Zhao; Yuxin Tu; Yaxin Che; Meilin Liu; Wei Wei; Zhifeng Xu; Hui Liu; Zhilou Liu (Chemical Engineering Journal, 2026)

Global radiative forcing assessment of brown carbon versus black carbon: Source-specific constraints from compiled observations - Shuhui Liu; Lei Li; Xindan Zhang; Yadong Lei; Haoling Zhang; Yu Zheng; Ke Gui; Hengheng Zhao; Jingrui Ma; Zhili Wang; Huizheng Che; Xiaoye Zhang (Atmospheric Environment, 2026)

Genome streamlining and functional adaptation of drought-enriched bacteria regulate soil heterotrophic respiration in alpine peatland - Yichang Gao; Yong Li; Zhongqing Yan; Kerou Zhang; Rongxiao Che; Lizhen Cui; Huan Wang; Yuechuan Niu; Enze Kang; Weirong Zhuang; Wenru Zhao; Miaomiao An; et al. (Plant and Soil, 2026)

Regulatory patterns and driving factors of soil aggregates on the environmental behavior of heavy metals: A global study based on meta-analysis and machine learning - Yu-Xuan Song; Yuhan Meng; Bingxuan Zhao; Tian-Hao Che; Zining Li; Zuozhou Yu; Xinyang Zhen; Yining Li; Chengyong Li; Quan-Ying Wang; Jing-Ya Zhou (Environmental Geochemistry and Health, 2026)

Wind Hazard Analysis of Typhoons Approaching Coastal China Based on the Typhoon Size Data - Zhenghao Wen; Lin Xue; Zhaozheng Che; Rui Zhang; Yanxia Zhao (Journal of Meteorological Research, 2026)

Numerical Simulation of Azimuthal Acoustic Logging-While-Drilling Responses for Geosteering Applications - Qi-qi Zhao; Lei Wang; Wen-xiao Qiao; Xiao-hua Che; Chao-deng Liu (Applied Geophysics, 2026)

Tetrabromobisphenol A and Cadmium Chloride Induced Hepatic Oxidative Stress and Autophagy Inhibition in Rats - Rongjing Sun; Jing Tian; Li Che; Tianyang Liu; Huibin Jin; Haonan Zhao; Jin Chen; Nianping Zhang; Xi Kang; Luqing Pan; Piaoye Wu; Bei Liu; et al. (Biological Trace Element Research, 2026)

NOTCH3 signal activation by its extracellular domain accumulation in an iPSC line newly established from a CADASIL patient - Ruihua Sun; Zhenxiang Zhao; Ningning Che; Ning Liu; Xiaoyi Ji; Anqi Li; Fengyu Wang; Junkui Shang; Jiewen Zhang (Human Cell, 2026)

Full-scale experimental study of flame behavior and thermal distribution in utility tunnel fires - Xiaojiang Liu; Zhao-Dong Xu; Jun Dai; Jiayu Che; Zhong-Wei Hu; Defu Che (Tunnelling and Underground Space Technology, 2026)

Partially etched Ti2AlN/Ti2N/TiN ternary composite as a synergistic catalyst for enhanced hydrogen storage kinetics and cycling stability of NaAlH4 - Chen Jin; Lingfeng Wang; Zhenke Chen; Hang Che; Shuzhong Wang; Zhiheng Liu; Tao Chen; Li Wang; Yuyuan Zhao; Xinhua Wang; Haoyuan Zheng; Haizhen Liu; et al. (Chemical Engineering Journal, 2026)

Dynamic mesh-based investigation of thermal environment during mars ascent vehicle launch phase - Zhongyi Sun; Zhanxun Che; Chengeng Zhao; Zeming Wang; Guigao Le (Advances in Space Research, 2026)

Characteristics and identification methods of acoustic reflected waves from borehole-intersected fractures - Bo Yang; Xiao-hua Che; Teng Zhao; Wen-xiao Qiao; Jun-qiang Lu; Bai-yong Men (Applied Geophysics, 2026)

Strategic directions for mitigating cultivated soil acidification in China: Insights from global progress and local practice - Ren Fang SHEN; Ying TENG; Jing CHE; Xueqiang ZHAO (Pedosphere, 2026)

Deposition characterization and predictive modeling of phosphorus and heavy metals during sewage sludge incineration - Qianqian Guo; Taojie Duan; Yanjun Hu; Long Jiao; Lingqin Zhao; Fan Yu; Xu Wang; Lei Che; Frederik Ronsse (Journal of Environmental Management, 2026)

Influence of free surface on microwave-induced rock fracturing: An experimental and numerical study - Yanlong Zheng; Ziqiang Su; Gaofeng Zhao; Ping Che; Jianchun Li (International Journal of Rock Mechanics and Mining Sciences, 2026)

A new pair of lunar gabbroic meteorites record magma recharge at ∼ 3.0 Ga - Peiyi Li; Yun Jiang; Kai Zhao; Shiyong Liao; Xiaochao Che; Xinru Zhang (Geochimica et Cosmochimica Acta, 2026)

Thermo-economic analysis and life cycle assessment of a poly-generation system based on HT-PEMFC, spray flash desalination and waste heat recovery - Benan Cai; Yuqi Zhao; Zaimin Guo; Ruihang Gao; Xunjian Che; Haijun Wang; Weihua Cai (Desalination, 2026)

Engineering active oxygen vacancy sites in WO3@COF for efficient photocatalytic hydrogen peroxide production - Yuheng Zhang; Qixin Pan; Chaojie Xing; Jiali Lu; Yunkai Sun; Xiaoqiang Xue; Wei Wang; Che Zhao; Rui Wang (Chemical Engineering Journal, 2026)

A novel spectral and phenological composite index for the early automatic mapping of potatoes from Sentinel-2 multi-temporal images - Lingang Wang; Yuan Gao; Yaozhong Pan; Wenjie Feng; Xingsheng Xia; Chuanwu Zhao; Xuechang Zheng; Hongyan Che; Yongsheng Huang; Xuehui Hou (Computers and Electronics in Agriculture, 2026)

Biocontrol eggplant soft rot caused by Fusarium equiseti through Bacillus amyloliquefaciens and its lipopeptides - Ping Zhou; Xilang Yang; Ziyun Xu; Xiaowei Che; Xiangjing Wang; Wensheng Xiang; Junwei Zhao (International Journal of Food Microbiology, 2026)

Mechanistic insights into Ti3CN MXene-modified NaAlH4: Boosting hydrogen storage kinetics and cyclability - Chen Jin; Zhenke Chen; Hang Che; Shuzhong Wang; Zhiheng Liu; Tao Chen; Li Wang; Yuyuan Zhao; Xinhua Wang; Haoyuan Zheng; Haizhen Liu; Mi Yan (Chemical Engineering Journal, 2026)

Mechanism of colloidal gas aphrons for enhanced reagent spreading and improved hydrophobicity of the surface of coal gasification fine slag - Daochang Che; Shengyu Liu; Fumin Zhao; Jianying Guo; Qilin Zhang; Xiaoyang Liu (Chemical Engineering Journal, 2026)

Synergistic CeH2.51/graphene nanointerface engineering for enhanced kinetics and cycling stability of Mg(NH2)2–2LiH - Chen Jin; Haoyuan Zheng; Lingfeng Wang; Zhenke Chen; Hang Che; Shuzhong Wang; Zhiheng Liu; Tao Chen; Li Wang; Yuyuan Zhao; Xinhua Wang; Haizhen Liu; et al. (Chemical Engineering Journal, 2026)

Soil texture modulates microbial responses to irrigation: Implications for nutrient cycling in arid agroecosystem - Kai Sun; Rong Yang; Zhuo Che; Wenzhi Zhao; Shujun Song; Haoqi Ren (Soil and Tillage Research, 2026)

Mechanistic insights into product distribution and bromine fixation during co-pyrolysis of cattle manure with organic components of printed circuit boards - Wenqi Guan; Dong Liang; Che Zhao; Danni Li; Shuxiao Wang; Rui Shan; Haoran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2026)

Phosphorus release and microbial community alterations in submerged areas of Qinghai Lake - Daye He; Yiming Zhao; Feifei Che; Shuhang Wang; Xia Jiang; Fuwen Deng; Xufeng Mao; Zheng Yu; Yunyan Guo (Gondwana Research, 2026)

Multifactorial impacts on ash behaviors during oxy-fuel co-combustion of semi-coke and biomass - Jinping Zhang; Wenwen Wei; Haichen Zhao; Siyuan Li; Jingchun Shen; Defu Che; Lei Chen (Fuel, 2026)

Organic substitution for synthetic fertilizer mitigates the negative effects of warming on soil quality, greenhouse gas emissions, and soybean yields - Xiaoyu Wang; Jiangsen Chu; Mengyou Zhang; Mingjun Hou; Ke Zheng; Leili Lin; Zhengjun Yan; Xiaoxiao Li; Zhao Che; He Song; Gong Wu (Field Crops Research, 2026)

Mechanosensor YAP orchestrates human neural rosette morphogenesis via TEAD4-LEF1 transcriptional nexus - Jinghao Hu; Zan He; Huifang Hu; Xiaoyan Sun; Shanshan Che; Shuhui Sun; Miyang Ma; Yixin Zhang; Shuai Ma; Weiqi Zhang; Juan Carlos Izpisua Belmonte; Guoguang Zhao; et al. (Science China Life Sciences, 2026)

Multi-proxy reconstruction of Holocene sedimentary evolution in the Yangtze Delta: Climatic forcing, sea-level oscillations, and diagenetic overprint - Zixuan Che; Chunzhu Chen; Lisi Wei; Wenwei Zhao; Quan Li; Yunpeng Yang; Hanfei Yang; Zhigang Wang; Xiaojian Zhang; Ximing Zhang; Shutong Yang; Huan Li; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Machine learning framework to enhance the predictive performance of the relative availability of heavy metals in soils around a gold mine in Hainan Island - Xiaoyu Wang; Yajing Qu; Feifei Che; Wenhao Zhao; Yifei Gao; Jin Ma; Fengchang Wu (Journal of Hazardous Materials, 2026)

Sustainable soil management in acidic paddy fields: liming and biochar application reduce greenhouse gas emissions while enhancing rice yields - Gong Wu; Xiaoyu Wang; Xing Wei; Mengyou Zhang; Jiangseng Chu; Mingjun Hou; Leili Lin; Yang Chen; Zhao Che; Xiaoxiao Li; Can Zhang; He Song (Journal of Environmental Management, 2026)

Impact of preceding winter sea surface temperature on the spring smoke aerosol dipole over the Indochina Peninsula - Yurun Liu; Ke Gui; Quanliang Chen; Liangliang Feng; Hengheng Zhao; Ruowen Yang; Huizheng Che (Atmospheric Research, 2026)

Mechanism of anomalous “internal subsidence and peripheral uplift” in a salt mine goaf: A multi-source validated superposition of poroelastic uplift and mining-induced subsidence - Ahu Zhao; Yinping Li; Xilin Shi; Shefeng Hao; Zengguang Che; Kun Yang; Mingnan Xu; Hongling Ma (Geomechanics for Energy and the Environment, 2025)

Novel insight into the heavy metal immobilization by coal fly ash-based geopolymers using machine learning and density functional theory - Kaizhi Yang; Bo Yang; Kezhou Yan; Yining Su; Longyi Zhao; Jungang Tang; Yu Che; Yanxia Guo (Waste Management, 2025)

Simulation study on mineral transformation behaviors and ash fusion characteristics during high-alkali coal combustion under deep peaking conditions - Jiamiao Liu; Guowei Ma; Yongbo Du; Chang’an Wang; Yonggang Zhao; Wanzhu Wu; Longping Shi; Lin Zhao; Defu Che (Fuel, 2025)

Preparation of stir bars coated with N-modified COFs and application to estrogen detection in dairy products - Xixi Lian; Lianzhi Wang; Jianing Sun; Yingying Fu; Zhengchao Duan; Yazhuo Wang; Che Zhao; Gangqi Cheng; Rui Shan (Food Chemistry, 2025)

Metastructure for broadband vibration suppression and ultra-low frequency energy harvesting by integrating intercell negative stiffness mechanism with 2-DOF oscillators - Zilong An; Che Xu; Chun H. Wang; Shuhua Peng; Yaowen Yang; Junlei Wang; Liya Zhao (Engineering Structures, 2025)

Investigation of the impact of local tumor phenolic-chemistry for dual starvation and vaccination therapy - Jingsong Lu; Zhenhu Guo; Sumei Chen; Ying Li; Xin Xu; Jing Yu; Shenglei Che; Guifeng Zhang; Wensheng Xie; Yen Wei; Lingyun Zhao (Chemical Engineering Journal, 2025)

Corrigendum to “Effect of molecular weight of chitosan and its oligosaccharides on antitumor activities of chitosan‑selenium nanoparticles” carbohydrate polymers, 2020, 231:115689 - Xiaoxiao Song; Yuying Chen; Guanghua Zhao; Hongbo Sun; Huilian Che; Xiaojing Leng (Carbohydrate Polymers, 2025)

Long-term variations in aerosol optical properties in Beijing: insights from diurnal and nocturnal continuous measurements - Shiya Peng; Yu Zheng; Lei Li; Ke Gui; Jibiao Zhu; Shuhui Liu; Haoling Zhang; Hujia Zhao; Huizheng Che; Xiaoye Zhang (Atmospheric Environment, 2025)

Machine learning of lithium and gallium accumulation based on the major element contents in coal gangue from Shanxi province coalfields - Kezhou Yan; Longyi Zhao; Kaizhi Yang; Yu Che; Yanxia Guo; Fangqin Cheng (Applied Geochemistry, 2025)

Factors influencing community residents’ participation intentions in habitat garden governance - Yue Zhu; Lingzhi Deng; Yuzhen Qian; Chenqi Zhang; Si Zhao; Yue Che (Urban Forestry & Urban Greening, 2025)

Glycosylation on breast cancer cell surface promotes the internalization and enhances therapeutic efficacy of cationic antimicrobial peptide L-K6 - Bo Wang; Yiwei Zhao; Qiuju Zhang; Jiaqi Zhao; Che Wang; Dejing Shang (Toxicology and Applied Pharmacology, 2025)

Optimization of sandwich panels with multi-layer aluminium foam for explosion-prevention converter transformer turrets - Chenguang Yan; Yiyao Lyu; Qinzhi Liu; Ke Wang; Yikun Zhao; Jiaxu Guo; Hao Liu; Che Xu (Process Safety and Environmental Protection, 2025)

The expansin-like gene StEXLB1 plays a role in potato defence against bacterial wilt - Dan Liu; Jiaqi Wang; Yexing Feng; Meng Luo; Zhixiang Xing; Yunzhu Che; Chong Du; Biao Zhao; Tianshuai Qi; Xiaocan Zhao; Fumeng He; Xu Feng; et al. (Plant Science, 2025)

Environmental nano-particulates induced pre-implantation embryonic toxicity in pluripotent stem cell-derived blastoids - Gaojing Liu; Yayuan Li; Xiuyun Liu; Wei Wang; Xiao Wen; Yange Che; Qiu Tu; Bo Zhao (Environmental Pollution, 2025)

Factors influencing the relationships between hourly visibility and aerosol optical depth in China—implications for hourly aerosol optical depth retrievals using automatic visibility observations - Nanxuan Shang; Ke Gui; Tiantao Cheng; Hengheng Zhao; Xutao Zhang; Wenrui Yao; Yu Zheng; Lei Li; Yurun Liu; Hong Wang; Zhili Wang; Huizheng Che; et al. (Atmospheric Environment, 2025)

Complexity of the NWA 773 Clan: New Evidence from Lunar Olivine Gabbro NWA 6950 - Qi He; Long Xiao; Ioannis Baziotis; Xiaochao Che; Yuqi Qian; Jiawei Zhao (Journal of Earth Science, 2025)

High-density magnetic-carbon interfaces in NiCu@C heterojunction toward broadband electromagnetic wave absorption - Zhikai Yan; Mengqiu Huang; Longjun Rao; Wenbin You; Biao Zhao; Lei Wang; Limin Wu; Ruixuan Zhang; Wei Li; Renchao Che (Chemical Engineering Journal, 2025)

Shifts in Bacterial Community Structure and Phosphorus-solubilizing Bacteria Abundance in Rhizosphere of Tibetan Barley along a Gradient of Soil Phosphorus Availability - Jing Che; Hao Zhou; Heng Zheng; Tongxin Zhao; Xing Liu (Journal of Soil Science and Plant Nutrition, 2025)
As the phosphorus (P) availability limits nutrient uptake and yield of crop plants, there is an urgent need to explore more P-solubilizing microorganisms and the influencing factors of their abundance in the field. However, it remains unclear how environmental and plant-related factors affect both total bacterial community and P-solubilizing bacteria in various P regime. In this study, we characterized the rhizosphere bacterial communities of Tibetan barley at 29 sites (classified into four soil types with varying AP contents) in a field survey as well as different barley origins in a field control experiment (located in Lasa and Linzhi) in China. We identified the P-solubilizing capacity of isolated bacterial strains in vitro and explored their distribution and relative abundance in the bacterial communities of Tibetan barley plants across sites and soil types. Our results found that Bacillus and Pseudomonas bacteria with the P-solubilizing capacity could be widely distributed in the rhizosphere of barley plants at different sites. Relative abundance of P-solubilizing bacteria and bacterial community structure, including the relative abundance of both dominant phyla and genera, OTUs richness, and Shannon index, varied greatly among the four soil types and was also related with soil available P content. These parameters were only affected by experimental location rather than plant seed origin, mainly due to a stronger influence of soil conditions in shaping root-associated bacterial community compared to plant-related factors. Overall, our study highlights the necessity of combining field survey and experimental approaches to explore the underlying mechanisms of plant-soil microorganism interactions.

Chemical constituents of the aerial parts of Mitracarpus hirtus (L.) DC (Rubiaceae) - Xinyi Wei; Yingrun Ma; Mingming Xu; Ding Heng; Monday M. Onakpa; Jin-Ao Duan; Chun-Tao Che; Hongkai Bi; Junfei Zhou; Ming Zhao (Natural Product Research, 2025)

Chalcocite-catalyzed Fenton coupling with biodegradation for N,N-dimethylformamide treatment: insights into mechanism and cost-effectiveness - Zhengqing Cai; Jiayi Zhao; Yanyu Song; Yongdi Liu; Long D. Nghiem; Jun Duan; Chengdan Che; Xianbo Sun (Journal of Cleaner Production, 2025)

Efficiently degradation of glyphosate and in-situ phosphorus recycle for promoting plant growth - Yuhao Zhao; Kaiye Gu; Huinan Che; Yanhui Ao (Environmental Research, 2025)

Effects of the southwest vortex on the vertical structure of ozone in the Sichuan Basin in China - Huiqiong Ning; Hong Wang; Ping Kang; Zhaodong Liu; Yue Peng; Wenjie Zhang; Chen Han; Yang Zhao; Wei Liu; Ping Wang; Huizheng Che (Atmospheric Pollution Research, 2025)

Chitosan/Gelatin/Carrageenan as a Composite Scaffolding Material for Cartilage Tissue Engineering - Chengyao Wang; Weiqin Zhao; Ning Ma; Linyu Chen; Jiajun Lu; Shuang Liu; Ziyi Wang; Huiju Hu; Hong Sun; Pengcheng Che (Journal of Medical and Biological Engineering, 2025)

Multi-objective optimization of inlet and outlet in a circular culture fish tank using the GBDT-NSGAII algorithm and computational fluid dynamic - Shanhong Zhang; Guanghui Yu; Yu Guo; Yang Wang; Daoliang Li; Xiaoli Zhao; Dannie D. O'Brien; Jui-Che Chiang (Aquacultural Engineering, 2025)

Urban park green spaces and their potential in regulating urban heat Island (UHI) effects in urban-rural gradient in Shanghai, China - Caihua Yang; Yifeng Qin; Hao Wu; Yangling Zhao; Shengquan Che (Sustainable Cities and Society, 2025)

Microwave-induced strength reduction and weakening mechanisms of basic rocks - Zhongjun Ma; Xiaobao Zhao; Han Li; Hanwen Liu; Yangwei Long; Yanlong Zheng; Ping Che (International Journal of Rock Mechanics and Mining Sciences, 2025)

Enhancement effect and mechanism of extraction of carbon from coal gasification fine slag Combining colloidal gas aphrons with bubble - Daochang Che; Shengyu Liu; Fumin Zhao; Jianying Guo; Lei Zhang (Chemical Engineering Journal, 2025)

A flexible intelligent sensor for patients with amyotrophic lateral sclerosis - Lei Duan; Zhi Li; Fan Jiang; Zong-Ju Chen; Wei-Song Zhang; Pei-Chen Zhao; Li-Chun Wang; Yan-Long Luo; Che Zhao; Cheng-Hui Li (Chemical Engineering Journal, 2025)

Hierarchically structured MOF aerogels with tandem pores for high-performance CO2 capture and separation - Yuhao Che; Chunqi Wang; Youlie Cai; Xue Wang; Tao Zhao; Aziz Bakhtiyarovich Ibragimov; Junkuo Gao (Chemical Engineering Journal, 2025)

Immobilization of Pb in Alkaline Soil Amend with Nano-hydroxyapatite: Speciation, Bioavailability, and Bioaccessibility - Kai Che; Jinxing Yu; Yukun Ju; Xuan Zhao; Yunqian Gong; Chongming Chen (Bulletin of Environmental Contamination and Toxicology, 2025)

Influence of asymmetrical features of scroll plates on thermodynamic processes and orbiting scroll dynamic characteristics of electric vehicle scroll compressors - Zibo Zhao; Che Wang; Jianhua Wu (International Journal of Refrigeration, 2025)

Investigating the impact of fecal contamination on antibiotic resistance genes in urban environments using host-associated molecular indicators - Yujing Duan; Hui She; Lingna Jing; Lianrui Duan; Jinxiu Zheng; Ying Shao; Yuxin Che; Yu Shi; Chao Guo; Wenhui Zhao; Tao Yang; Lijun Yang (Environmental Pollution, 2025)

Association of ambient ozone with time to pregnancy and the modifying effect of ambient temperature: a population-based cohort study - Bingxue Wu; Tao Wang; Yan Zhang; Yuyan Li; Cai Kong; Yishi Jiang; Xiangjing Song; Xing Chen; Zhengyuan Xie; Hanfeng Ye; Lin Feng; Zigao Zhao; et al. (Environmental Pollution, 2025)

Effects of monochromatic LED light quality on photosynthetic capacity and pigment content in Dunaliella salina under low light intensity - Tianze Zhao; Yongfu Li; Xingkai Che; Haixing Wu; Yuchen Ye; Dingning Fan; Zhendong Li; Yingjie Zhao; Wei Ye (Journal of Applied Phycology, 2025)

Spatial characteristics of microbial communities and their functions in sediments of subtropical Beibu Gulf, China - Wenxue Che; Hui Zhao; Ying Man; Xiao Tan (Marine Environmental Research, 2025)

Study on the contribution of the major desert groups on SDS weather in East Asia combining the model simulation and multiple observations - Huiqiong Ning; Hong Wang; Zhaodong Liu; Yue Peng; Wenjie Zhang; Chen Han; Yang Zhao; Ping Wang; Hailin Gui; Jikang Wang; Huizheng Che; Xiaoye Zhang (Atmospheric Research, 2025)

Study on Measurement Method and Influencing Factors of Surface Temperature for Rock Under Microwave Irradiation - Zhongjun Ma; Xiaobao Zhao; Shuo Yang; Yanlong Zheng; Yangwei Long; Ping Che (Rock Mechanics and Rock Engineering, 2025)

Selective preparation of aromatic compounds from catalytic pyrolysis polyester coating over Ni, Mo and Co metal modified ZSM-5 - Zhen-Qiang Yu; Yao-Xin Xiao; Dong Liang; Che Zhao; Zhen Huang; Gang-Qi Cheng; Rui Shan; Hao-Ran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Effects of residual carbon on slag flow characteristics of Zhundong high-alkali coal under oxy-fuel condition - Yuanmao Chen; Chang’an Wang; Maoyun Luo; Lin Zhao; Pengbo Zhao; Defu Che (Fuel, 2025)

Association between ambient temperature and couple fecundity: Insights from a large-scale cohort study in Yunnan, China - Bingxue Wu; Tao Wang; Yan Zhang; Yuyan Li; Xing Chen; Zhengyuan Xie; Cai Kong; Yuzhi Lan; Hanfeng Ye; Xiangjing Song; Zigao Zhao; Yan Che (International Journal of Hygiene and Environmental Health, 2025)

Revealing the mechanisms of rhamnolipid enhancing methane production from anaerobic digestion of bituminous coal - Shufeng Zhao; Hongyu Guo; Norbert Klitzsch; Daping Xia; Xiao Liu; Yan Liu; Ying Che (Biomass and Bioenergy, 2025)

Long-term distribution and evolution trends of absorption aerosol optical depth with different chemical components in global and typical regions - Hujia Zhao; Ke Gui; Yangfeng Wang; Yaqiang Wang; Hong Wang; Yu Zheng; Lei Li; Xiaofang Jia; Huizheng Che; Xiaoye Zhang (Atmospheric Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

High-precision U-series dating of Panxian Dadong hominin site, Guizhou Province, southwestern China - Xiaochao Che; Fei Han; Xingsheng Zhang; Bo Cao; Ping Xiao; Guanjun Shen; Jianxin Zhao (Quaternary Science Reviews, 2025)

Assessing the interaction of oceanic and riverine processes on coastal phytoplankton dynamics in the East China Sea - Jiawei Gao; Rong Bi; Julian P. Sachs; Yaoyao Wang; Yang Ding; Hong Che; Jing Zhang; Peng Yao; Jie Shi; Meixun Zhao (Marine Life Science & Technology, 2025)
The interaction of riverine inputs and ocean current systems causes complex spatiotemporal variations in phytoplankton dynamics in marginal seas of the northwest Pacific Ocean, yet quantitative assessments of these variations and their causes remain limited. Here we evaluate phytoplankton biomass and community structure changes using lipid biomarkers, accompanying ocean circulation and nutrient variations in surface waters collected in spring and summer of 2017–2018 at 118 sites in the East China Sea off the Zhejiang coast. High biomass of diatoms, inferred from brassicasterol concentrations, shifted from the south in spring to the north in summer, while high dinoflagellate biomass, inferred from dinosterol concentrations, occurred mainly in the Changjiang (Yangtze) River plume and adjacent areas in both seasons. Seasonal variation in phytoplankton distribution was linked to the spatial extents of water masses such as the Changjiang Diluted Water (CDW) and the intrusion of the Kuroshio Subsurface Water (KSSW). A three end-member mixing model was applied to quantify water mass contributions. The results showed that an increase in the KSSW (from 0 to 40%) and a decrease in the CDW (from 100 to 20%) resulted in a significant (20%) increase in diatom proportions and a significant (20%) decrease in dinoflagellate proportions. Dinoflagellate proportions were highest in the CDW-dominated region, while diatoms and total phytoplankton biomass were higher in the CDW–KSSW mixing region and the KSSW-dominated region. This study highlights the dynamic response of the phytoplankton community to water mass changes in marginal seas that can aid coastal ecosystem management.

Optimization of an anti-recoil control scheme based on improved NSGA-II for a deep-water drilling riser after emergency disconnection - Shuai Meng; Guixin Zhao; Chidong Che (Ocean Engineering, 2025)

A comprehensive molecular phylogeny of the genus Sylvirana (Anura: Ranidae) highlights unrecognized diversity, revised classification and historical biogeography - Yun-He Wu; Man-Hao Xu; Chatmongkon Suwannapoom; Sang Ngoc Nguyen; Robert W. Murphy; Theodore J. Papenfuss; Amy Lathrop; Felista Kasyoka Kilunda; Wei Gao; Zhi-Yong Yuan; Jin-Min Chen; Liang Zhang; et al. (Molecular Phylogenetics and Evolution, 2025)

Experimental study on characteristics and mechanism of hydrogen production from aluminium–water reaction for carbon-free power generation - Xinyue Gao; Chang’an Wang; Yujie Hou; Lin Zhao; Wengang Bai; Defu Che (Fuel, 2025)

Photo-motivated heterojunctions coupling built-in electric field stimulating sulfur redox kinetics for lithium-sulfur batteries - Haifeng Zhang; Fei Ma; Ting Meng; Junwei Li; Haifei Zhu; Zeyu Geng; Wenbo Zhao; Xiaohan Wang; Penghui Wu; Abdelnaby M. Elshahawy; Qianrui Gao; Quande Che (Chemical Engineering Journal, 2025)

Mechanical properties and interfacial adhesion mechanism of polyolefin composites reinforced with ethylene vinyl alcohol-coated cellulose microfibers - Yixin Zhao; Shuya Zhang; Lei Zhang; Mingda Che; Renliang Huang; Mei Cui; Wei Qi; Rongxin Su (Chemical Engineering Journal, 2025)

Triple modifications of Li-rich manganese-based cathode materials using LiMnPO4 one-step method - Jianan Hao; Jinyang Dong; Yuefeng Su; Kang Yan; Jiayu Zhao; Huiquan Che; Yun Lu; Ning Li; Bin Zhang; Ping Zhang; Feng Wu; Lai Chen (Chemical Engineering Journal, 2025)

Enlarged scars: The effects of economic policy uncertainty on electricity accessibility and urban-rural disparity - Congyu Zhao; Xuan Zhai; Miaomiao Tao; Shuai Che (Utilities Policy, 2024)

Partial organic substitution increases soil quality and crop yields but promotes global warming potential in a wheat-maize rotation system in China - Gong Wu; Hai-meng Huang; Bei-bei Jia; Lei-lei Hu; Chong-sheng Luan; Qi Wu; Xiao-yu Wang; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Soil and Tillage Research, 2024)

Environmental changes and human impacts over the past 1200 years: Evidence from high-resolution pollen records from peat in the Yunnan-Guizhou Plateau, Southwest China - Shuming Li; Lisi Wei; Wenwei Zhao; Weihe Ren; Qinran Gu; Zixuan Che; Xianyong Cao; Huan Li; Xiaojian Zhang; Chunzhu Chen; Yan Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Investigation of discharge valve in ultra-high-speed rotary compressors: An experimental and FSI simulation-based study - Hua Zhong; Wei Zhao; Zhaodong Zhang; Che Wang; Keke Gao; Jianhua Wu (International Journal of Refrigeration, 2024)

Estimating AVHRR snow cover fraction by coupling physical constraints into a deep learning framework - Qin Zhao; Xiaohua Hao; Tao Che; Donghang Shao; Wenzheng Ji; Siqiong Luo; Guanghui Huang; Tianwen Feng; Leilei Dong; Xingliang Sun; Hongyi Li; Jian Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Experimental study and chemical equilibrium calculation on the mineral transformation of high-alkali coal under oxy-fuel condition - Lin Zhao; Chang’an Wang; Yingchao Nie; Yongxu Chen; Jinming Zhang; Maoyun Luo; Defu Che (Fuel, 2024)

A Kirkendall strategy for the efficient degradation of trichloroethylene from groundwater using cellulose nanofiber-supported sulfidated nZVI - Mingda Che; Jingzhe Xiao; Shuya Zhang; Cancan Shan; Ze Zhao; Renliang Huang; Yitong Zhou; Mei Cui; Wei Qi; Rongxin Su (Chemical Engineering Journal, 2024)

Breast cancer therapy: from the perspective of glucose metabolism and glycosylation - Jiaqi Zhao; Haiting Sun; Che Wang; Dejing Shang (Molecular Biology Reports, 2024)

MiR-497-5p ameliorates the oxyhemoglobin-induced subarachnoid hemorrhage injury in vitro by targeting orthodenticle homeobox protein 1 (Otx1) to activate the Nrf2/HO-1 pathway - Jun Zhu; Enyu Pan; Lujun Pang; Xiwei Zhou; Yanjun Che; Zhao Liu (Molecular Genetics and Genomics, 2024)

Establishment and Validation of Sandell-Kolthoff Method for Saliva Iodine Determination - Yue Su; Ming Li; Honglei Xie; Xin Hou; Meng Zhao; Jia Li; Haowen Pan; Zexu Zhang; Zongyu Yue; Wenjing Che; Lanchun Liu; Jiasen Cao; et al. (Biological Trace Element Research, 2024)

Effects of filter-feeding fish faeces on microbial driving mechanism of lake sediment carbon transformation - Yiming Li; Xuan Che; Hongyuan Chen; Zhanpeng Meng; Xinfeng Li; Xiaodong Wang; Lin Zhu; Yunlong Zhao (Science of The Total Environment, 2024)

Copper/iron bimetal phenolic networks boosted apoptosis/ferroptosis/cuproptosis combined tumor therapy through dual glutathione depletion - Fan Zhao; Hongyan Yu; Chen Wang; Junchen Xu; Hao Gao; Yao Ying; Wangchang Li; Juan Li; Jingwu Zheng; Liang Qiao; Shenglei Che; Jing Yu (Chemical Engineering Journal, 2024)

Structural reconstruction of lignin by mild and efficient dissolution: A strategy for the fabrication of mechanically strong carbon fiber precursors - Ruimin Che; Hui Zhao; Xin Li; Deqiang Li; Haq Nawaz; Feng Xu (Chemical Engineering Journal, 2024)

Tunicate cellulose nanocrystals strengthened injectable stretchable hydrogel as multi-responsive enhanced antibacterial wound dressing for promoting diabetic wound healing - Shengming Hua; Yujie Zhang; Yifei Zhu; Xin Fu; Lingtao Meng; Lihua Zhao; Lingming Kong; Shihui Pan; Yuju Che (Carbohydrate Polymers, 2024)

Population exposure disparities between residential and working areas during a cold wave event in Changchun, China - Hongchao Xu; Peng Zeng; Fengyun Sun; Hongyu Zhao; Yue Che (Applied Geography, 2024)

Accurately estimate soybean growth stages from UAV imagery by accounting for spatial heterogeneity and climate factors across multiple environments - Yingpu Che; Yongzhe Gu; Dong Bai; Delin Li; Jindong Li; Chaosen Zhao; Qiang Wang; Hongmei Qiu; Wen Huang; Chunyan Yang; Qingsong Zhao; Like Liu; et al. (Computers and Electronics in Agriculture, 2024)

Transcriptomic analysis reveals nanoplastics-induced apoptosis, autophagy and immune response in Litopenaeus vannamei - Yiming Li; Yucong Ye; Xiaoyi Zhu; Xingguo Liu; Xinfeng Li; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

A dynamic risk assessment method for ship conflict based on imperfect information game theory - Jie Zhao; Shengkui Zeng; Jianbin Guo; Haiyang Che (Ocean Engineering, 2024)

Decreased soil pH weakens the positive rhizosphere effect on denitrification capacity - Jun WANG; Zongxiang ZHANG; Fei LIANG; Zhao CHE; Yongkang WEN; Manyu ZHANG; Wenjun JIN; Zhaorong DONG; He SONG (Pedosphere, 2024)

Enhanced reductive catalytic fractionation of lignocellulose using a water-resistant RuNiZnOx/Nb2O5 catalyst with synergistic hydrogen spillover and acidic properties - Zhaozhuo Yu; Wenzhuo Kong; Yaping Guo; Wen Liang; Jiawei Liang; Meijuan Chen; Dongxu Zhao; Hongzhen Ma; Xiangjun Liu; Solomon Inalegwu Okopi; Lei Che; Qi Zhang; et al. (Fuel, 2024)

2D metal borides (MBenes): Synthesis methods for energy storage applications - Abdul Jabbar Khan; Syed Shaheen Shah; Shaukat Khan; Abdul Mateen; Bushra Iqbal; Mizna Naseem; Liang He; Yi Zhang; Yong Che; Ya Tang; Miao Xu; Ling Gao; et al. (Chemical Engineering Journal, 2024)

Influence of film color, mulching ratio and soil–mulch contact degree on heat transfer in Northwest China - Yin Zhao; Zunqiu Xu; Xiaomin Mao; Sien Li; Xingchao Qi; Jiangang Che (Agricultural and Forest Meteorology, 2024)

Unraveling novel umami peptides from yeast extract (Saccharomyces cerevisiae) using peptidomics and molecular interaction modeling - Chunyu Gao; Rilei Yu; Xiaomei Zhang; Xue Song; Lizhi Che; Yuying Tang; Jinyue Yang; Jing Hu; Jian Xiong; Xue Zhao; Hongwei Zhang (Food Chemistry, 2024)

Formation of conjugated polymer/TiO2(B) S-scheme heterojunctions by functional group regulation for efficient natural light-driven inactivation of super-resistant bacteria - Xin Zhao; Simiao Wang; Diyang Shan; Ying Xu; Lina Wu; Haiyong Guo; Guangbo Che; Chunbo Liu; Juan Du (Chemical Engineering Journal, 2024)

Relative contributions of component-segregated aerosols to trends in aerosol optical depth over land (2007–2019): Insights from CAMS aerosol reanalysis - Hengheng Zhao; Ke Gui; Wenrui Yao; Nanxuan Shang; Xutao Zhang; Yuanxin Liang; Yurun Liu; Lei Li; Yu Zheng; Zhili Wang; Hong Wang; Junying Sun; et al. (Atmospheric Environment, 2024)

Monitoring nonlinear large gradient subsidence in mining areas through SBAS-InSAR with PUNet and Weibull model fusion - Yuanjian Wang; Ximin Cui; Chunqing Ge; Yuhang Che; Yuling Zhao; Peixian Li; Yue Jiang; Xiaoqing Han (Environmental Science and Pollution Research, 2024)

Non-radical activation of persulfate with Bi2O3/BiO1.3I0.4 for efficient degradation of propranolol under visible light - Yuehua Deng; Qianqian Che; Yani Li; Jiating Luo; Xiang Gao; Yan He; Yiling Liu; Tong Liu; Xiaolong Zhao; Xiaobin Hu; Wei Zhao (Journal of Environmental Sciences, 2024)

Construction of chiral magnetic structure with enhancement in magnetic coupling for efficient Low-Frequency microwave absorption - Hao Zhang; Yongpeng Zhao; Mingyue Yuan; Chen Sun; Hui Huang; Yuchen Jiang; Zeng Fan; Renchao Che; Lujun Pan (Chemical Engineering Journal, 2024)

Study on the cavity evolution and load characteristics of large projectile during high-speed water entry - Peiqi Che; Yao Shi; Hairui Zhao; Yilan Yu; Guang Pan (Ocean Engineering, 2024)

Polystyrene microplastics enhance microcystin-LR-induced cardiovascular toxicity and oxidative stress in zebrafish embryos - Yuchun Xiao; Liwen Hu; Jiayao Duan; Huimin Che; Wenxin Wang; Yuan Yuan; Jiayi Xu; Daojun Chen; Sujuan Zhao (Environmental Pollution, 2024)

Dietary lipid supplementation alleviated the impacts of polystyrene nanoplastic exposure in Litopenaeus vannamei - Yiming Li; Yucong Ye; Haojuan Yuan; Siwen Li; Na Rihan; Xingguo Liu; Yunlong Zhao; Xuan Che (Aquatic Toxicology, 2024)

Heating and Water Transport Behavior of Sandstones Under Microwave Irradiation - Qinhua Zhao; Yanlong Zheng; Jianchun Li; Ping Che; Xiaobao Zhao (Rock Mechanics and Rock Engineering, 2024)

The multi-year contribution of Indo-China peninsula fire emissions to aerosol radiation forcing in southern China during 2013–2019 - Jun Zhu; Xu Yue; Hao Zhou; Huizheng Che; Xiangao Xia; Jun Wang; Tianliang Zhao; Chenguang Tian; Hong Liao (Science of The Total Environment, 2024)

Boosting photocatalytic activity in ternary lamellar hierarchical structured ZnFe2O4/polymeric carbon nitride by constructing an electronic bridge - Youhai Zhao; Zishuang Guo; Yucheng Wang; Martin Birkett; Xiao Xiang; Chengang Zhang; Yaran Jin; Guangbo Che; Haiwang Wang; Chunbo Liu; Terence Xiaoteng Liu; Jian Qi (Journal of Environmental Chemical Engineering, 2024)

Experimental study on sewage collection and related performance of square arc angle aquaculture tank - Zonglong Che; Yinxin Zhou; Chenxu Zhao; Xiaozhong Ren; Hangfei Liu; Wei Sun; Haibo Liu; Meng Li (Aquaculture International, 2024)

Vertical distributions of lipid biomarkers in spring and summer in coastal regions of the East China Sea - Jiawei Gao; Shulan Xu; Rong Bi; Yaoyao Wang; Yang Ding; Hong Che; Jing Zhang; Peng Yao; Jie Shi; Meixun Zhao (Frontiers in Marine Science, 2024)
Lipid biomarkers are amongst the most widely used proxies in studies of the structure and functioning of marine food webs. However, vertical distributions of lipid biomarkers and their controlling mechanisms remain unclear, especially in highly dynamic coastal ecosystems. Here we tested vertical profiles of key lipid biomarkers (sterols and fatty acids) in suspended particles and their correlations with water masses in spring of 2017 and summer of 2018 in the Zhejiang coasts of the East China Sea. The Changjiang Diluted Water, the Taiwan Strait Water and the Kuroshio Subsurface Water showed strong contributions in the surface layer in spring, the surface layer in summer, and the deep layer in both seasons, respectively. Accordingly, lipid biomarker composition also varied between different water layers. Overall, lipid biomarker concentrations in the surface layer were around 2 ~ 7 times higher than those in the deep layer, indicating high phytoplankton biomass in the surface layer. The ratio of docosahexaenoic acid to eicosapentaenoic acid was also higher in the surface layer, especially in the south of our study region, suggesting high nutritional quality of particulate organic matters in the surface layer. Significant correlations between the depth profiles of lipid biomarkers and water masses suggested the control of water masses on lipid biomarker production. The distribution patterns of lipid biomarkers in our study are consistent with previous findings on zooplankton grazing and fish larvae, highlighting the significance of lipid biomarkers as trophic markers to study food web structure and functioning in highly dynamic coasts.

Effects of SO2 and H2O on the ash deposition and NO emission during oxy-fuel combustion of high-alkali coal - Lin Zhao; Chang’an Wang; Tianlin Yuan; Liangxu Dai; Yingchao Nie; Guowei Ma; Lei Zhou; Maoyun Luo; Defu Che (Process Safety and Environmental Protection, 2024)

Influence of low-density polyethylene addition on nitrogen transformation during sludge protein pyrolysis - Shuai Guo; Yu Wang; Jianwen Yi; Deng Zhao; Deyong Che; Hongpeng Liu; Baizhong Sun (Process Safety and Environmental Protection, 2024)

Experimental investigation and numerical modeling of effect of specimen size on microwave-induced fracturing of diorite - Zhongjun Ma; Yanlong Zheng; Fuxin Rui; Gaofeng Zhao; Jianchun Li; Ping Che (Minerals Engineering, 2024)

Experimental study on metal removal characteristics of Zhundong coal to produce ultra-clean coal using acid-alkali method - Yuanmao Chen; Chang'an Wang; Yang Li; Maoyun Luo; Chenglong Yang; Lin Zhao; Zhefan Wang; Ning Fu; Defu Che (Fuel, 2024)

Three-dimensional structure and transport flux of springtime smoke aerosols over the Indochina Peninsula - Yurun Liu; Ke Gui; Quanliang Chen; Liangliang Feng; Hongke Cai; Xutao Zhang; Wenrui Yao; Hengheng Zhao; Nanxuan Shang; Lei Li; Yu Zheng; Huizheng Che (Atmospheric Research, 2024)

Gender disparities in summer outdoor heat risk across China: Findings from a national county-level assessment during 1991–2020 - Peng Zeng; Dachuan Shi; Marco Helbich; Fengyun Sun; Hongyu Zhao; Yaoyi Liu; Yue Che (Science of The Total Environment, 2024)

Exposure to polystyrene nanoplastics induces apoptosis, autophagy, histopathological damage, and intestinal microbiota dysbiosis of the Pacific whiteleg shrimp (Litopenaeus vannamei) - Yiming Li; Yucong Ye; Haojuan Yuan; Na Rihan; Mingming Han; Xingguo Liu; Tian Zhu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

Continuous flow combined with in situ self-assembly fabrication of high permselective ZIF-8@GO composite membrane in ceramic tube for organic dye nanofiltration - Xunke Zhao; Kaihuan Nie; Fuyi Sun; Cheng Xie; Yanran Cheng; Yuanyuan Che (Process Safety and Environmental Protection, 2024)

Does climate aid alleviate carbon lock-in? A global perspective - Congyu Zhao; Xiaoyue Ma; Shuai Che; Zhengguang Liu; Chenchen Song (Journal of Cleaner Production, 2024)

Common vetch intercropping with reduced irrigation ensures potato production by optimizing microbial interactions - Ting Che; Xinyue Zhang; Mingyue He; Fei Wang; Na Li; Xiayun Zang; Zhuoliang Xiao; Yuanzhou Xu; Feng Hu; Yongfeng Ren; Huijuan Zhang; Li Xu; et al. (Field Crops Research, 2024)

Partial organic substitution for synthetic fertilizer improves soil fertility and crop yields while mitigating N2O emissions in wheat-maize rotation system - Gong Wu; Shuo Yang; Chong-sheng Luan; Qi Wu; Lei-li Lin; Xiao-xiao Li; Zhao Che; De-bao Zhou; Zhao-rong Dong; He Song (European Journal of Agronomy, 2024)

The application study of the revised IMPROVE atmospheric extinction algorithm in atmospheric chemistry model focusing on improving low visibility prediction in eastern China - Chen Han; Hong Wang; Yue Peng; Zhaodong Liu; Wenjie Zhang; Yang Zhao; Huiqiong Ning; Ping Wang; Huizheng Che (Atmospheric Research, 2024)

Columnar optical-radiative properties and components of aerosols in the Arctic summer from long-term AERONET measurements - Yuanxin Liang; Huizheng Che; Xindan Zhang; Lei Li; Ke Gui; Yu Zheng; Xutao Zhang; Hengheng Zhao; Peng Zhang; Xiaoye Zhang (Science of The Total Environment, 2024)

Polystyrene nanoplastics exposure alters muscle amino acid composition and nutritional quality of Pacific whiteleg shrimp (Litopenaeus vannamei) - Yiming Li; Yucong Ye; Na Rihan; Bihong Zhu; Qichen Jiang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

The mechanism of photothermal catalytic reforming of biomass tar: An exploratory study based on density functional theory - Beibei Yan; Tianxiao Yu; Jian Li; Xiaopeng Jia; Zhiyu Li; Yuechi Che; Guanyi Chen; Juan Zhao (Fuel, 2024)

Responses of radial growth to climate change for two dominant artificial coniferous trees - Jingrong Su; Shengchun Xiao; Xiaomei Peng; Cunwei Che; Peng Zhao (Dendrochronologia, 2024)

Experimental study and techno-economic analysis of co-processing system for treatment of food waste with various impurities - Solomon Inalegwu Okopi; Jiayu Wang; Wen Liang; Wenzhuo Kong; Yang Hu; Jiahao Cui; Xinyang Guo; Weiwei Zhao; Lei Che; Zhaolin Gu; Fuqing Xu (Bioresource Technology, 2024)

Efficient composite chlorinated ethenes removal using gallic acid to enhance Fe/Ni nanoparticles activated persulfate - Mingda Che; Hongjian Su; Huimin Si; Bin Guo; Renliang Huang; Jing Zhao; Rongxin Su (Environmental Science and Pollution Research, 2024)

Polystyrene nanoplastics induce lipid metabolism disorder and alter fatty acid composition in the hepatopancreas of Pacific whiteleg shrimp (Litopenaeus vannamei) - Yiming Li; Yucong Ye; Na Rihan; Bihong Zhu; Qichen Jiang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

Projections of Greenland climate change from CMIP5 and CMIP6 - Qinglin Zhang; Baojuan Huai; Minghu Ding; Weijun Sun; Weigang Liu; Jinpei Yan; Shuhui Zhao; Yetang Wang; Yuzhe Wang; Lei Wang; Jiahang Che; Jiahui Dou; et al. (Global and Planetary Change, 2024)

Aerosol optical and radiative properties and their environmental effects in China: A review - Huizheng Che; Xiangao Xia; Hujia Zhao; Lei Li; Ke Gui; Yu Zheng; Jingjing Song; Bing Qi; Jun Zhu; Yucong Miao; Yaqiang Wang; Zhili Wang; et al. (Earth-Science Reviews, 2024)

Soil pH differently affects N2O emissions from soils amended with chemical fertilizer and manure by modifying nitrification and denitrification in wheat-maize rotation system - Gong Wu; Fei Liang; Qi Wu; Xiao-Gang Feng; Wen-ding Shang; Hua-wei Li; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Biology and Fertility of Soils, 2024)

Quantitative proteomics reveals the neurotoxicity of trimethyltin chloride on mitochondria in the hippocampus of mice - Zhenzhong Liu; Li Wang; Yue Wang; Siya Wu; Caiting Peng; Yu Wang; Ming Huang; Li Che; Rongjing Sun; Xi Zhao; Zuo Du; Wenhu Liu (NeuroToxicology, 2023)

From cellulose to tar: Analysis of tar formation pathway with distinguishing the primary and secondary reactions - Xiaopeng Jia; Yuechi Che; Jian Li; Beibei Yan; Zhanjun Cheng; Guanyi Chen; Juan Zhao (Bioresource Technology, 2023)

Structural characteristics variations of dough incorporated with long-chain inulin modified by phosphorylation - Yingyu Zhao; Denglin Luo; Chonghui Yue; Libo Wang; Peiyan Li; Zhouya Bai; Jiaxin Che (Journal of Cereal Science, 2023)

Organohydrogels with cellulose nanofibers enhanced supramolecular interactions toward high performance self-adhesive sensing pads - Cancan Shan; Lukas Bauman; Mingda Che; A-Reum Kim; Rongxin Su; Boxin Zhao (Carbohydrate Polymers, 2023)

Structurally diverse (9β-H)-pimarane derivatives with six frameworks from the leaves of Icacina oliviformis and their cytotoxic activities - Mingming Xu; Di Di; Lu Fan; Yingrun Ma; Xinyi Wei; Er-Xin Shang; Monday M. Onakpa; Oluwatosin O. Johnson; Jin-Ao Duan; Chun-Tao Che; Junfei Zhou; Ming Zhao (Phytochemistry, 2023)

Study on the temperature distribution of motor and inverter in an electric scroll compressor for vehicle air conditioning under refrigeration conditions - Shuai Zhang; Che Wang; Hua Zhong; Zibo Zhao; Jianyuan Feng; Qihang Wu; Jianhua Wu (International Journal of Refrigeration, 2023)

Development of a recurrent spatiotemporal deep-learning method coupled with data fusion for correction of hourly ozone forecasts - Jie Li; Ji-cheng Jang; Yun Zhu; Che-Jen Lin; Shuxiao Wang; Jia Xing; Xinyi Dong; Jinying Li; Bin Zhao; Bingyao Zhang; Yingzhi Yuan (Environmental Pollution, 2023)

Evolutions of dissolved organic matter and disinfection by-products formation in source water during UV-LED (275 nm)/chlorine process - Xiating Zhao; Chuze Chen; Haoran Chen; Yaxin Guo; Xueqi Zhang; Mengting Li; Liu Cao; Yuting Wang; Tingting Gong; Lei Che; Guoying Yang; Qiming Xian (Water Research, 2023)

Polystyrene nanoplastics decrease nutrient accumulation, disturb sex hormones, and inhibit reproductive development in juvenile Macrobrachium nipponense - Yiming Li; Yucong Ye; Na Rihan; Qichen Jiang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2023)

Decomposition of meteorological and anthropogenic contributions to near-surface ozone trends in Northeast China (2013–2021) - Nanxuan Shang; Ke Gui; Hujia Zhao; Wenrui Yao; Hengheng Zhao; Xinglu Zhang; Xutao Zhang; Lei Li; Yu Zheng; Zhili Wang; Yaqiang Wang; Huizheng Che; et al. (Atmospheric Pollution Research, 2023)

A late Neoproterozoic to early Paleozoic accretionary orogenic belt in the eastern Central Asian orogenic Belt: Evidence from the Irshi ophiolite mélange in the middle segment of the Great Xing’an Range - Jianfeng Liu; Jinyi Li; Shuo Zhao; Maohui Ge; Yawen Che (Journal of Asian Earth Sciences, 2023)

Pan-genome analysis of the Burkholderia gladioli PV. Cocovenenans reveal the extent of variation in the toxigenic gene cluster - Hao Gong; Xiuli Huang; Wenjuan Zhu; Jiacong Chen; Yongde Huang; Zhifeng Zhao; Jia Weng; Yuhui Che; Jiangyong Wang; Xiaoqin Wang (Food Microbiology, 2023)

Propineb induced notochord deformity, craniofacial malformation, and osteoporosis in zebrafish through dysregulated reactive oxygen species generation - Wei Yuan; Ying Hu; Chen Lu; Jun Zhang; Ye Liu; Xinran Li; Kun Jia; Yong Huang; Zekun Li; Xiaomei Chen; Fei Wang; Xiaokun Yi; et al. (Aquatic Toxicology, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Hexavalent chromate bioreduction by a magnetotactic bacterium Magnetospirillum gryphiswaldense MSR-1 and the effect of magnetosome synthesis. - Siang Chen Wu; Wei-Che Hsiao; Ya-Chun Zhao; Li-Fen Wu (Chemosphere, 2023)

Two genes related to apoptosis in the hepatopancreas of juvenile prawn, Macrobrachium nipponense: Molecular characterization and transcriptional response to nanoplastic exposure - Yiming Li; Xinglin Du; Wen Li; Qichen Jiang; Yucong Ye; Ying Yang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2023)

A novel magnetic buoyant-bead flotation method for the removal of typical microalgae from harmful algal blooms - Yan Zhao; Xuexue Wu; Wenjuan Chang; Wenlu Che; Yi Liu; Yanpeng Li (Journal of Environmental Chemical Engineering, 2023)

The combined effects of heterogeneous chemistry and aerosol-radiation interaction on severe haze simulation by atmospheric chemistry model in Middle-Eastern China - Zhaodong Liu; Hong Wang; Yue Peng; Wenjie Zhang; Huizheng Che; Yangmei Zhang; Hongli Liu; Yaqiang Wang; Mengchu Zhao; Xiaoye Zhang (Atmospheric Environment, 2023)

Seasonal evolution of aerosol loading and its vertical distribution in northeastern China from long-term satellite observations and model reanalysis - Hujia Zhao; Ke Gui; Yanjun Ma; Yangfeng Wang; Yaqiang Wang; Hong Wang; Yu Zheng; Lei Li; Lei Zhang; Huizheng Che; Xiaoye Zhang (Atmospheric Environment, 2023)

Hydrogen Gas Enhanced Seed Germination by Increasing Trehalose Biosynthesis in Cucumber - Panpan Huang; Changxia Li; Pengpeng Che; Huwei Liu; Zongxi Zhao; Li Feng; Xinjuan Liu; Weibiao Liao (Journal of Plant Growth Regulation, 2023)

Impact of commercial cooking on urban PM2.5 and O3 with online data-assisted emission inventory - Yingzhi Yuan; Yun Zhu; Che-Jen Lin; Shuxiao Wang; Yanghong Xie; Haixian Li; Jia Xing; Bin Zhao; Mengmeng Zhang; Zhiqiang You (Science of The Total Environment, 2023)

Study on the contact and size of radial and flank leakage gaps of scrolls in a scroll compressor with CFD/CSM simulations - Che Wang; Shuai Zhang; Zibo Zhao; Junming Cheng; Jianhua Wu (International Journal of Refrigeration, 2023)

Investigation on Co-combustion characteristics and NO emissions of coal and municipal sludge in a tangentially fired boiler - Chang'an Wang; Meijing Chen; Pengbo Zhao; Lei Zhou; Yujie Hou; Jinming Zhang; Qiang Lyu; Defu Che (Fuel, 2023)

Description and evaluation of a newly developed emission inventory processing system (EMIPS) - Wencong Chen; Yaqiang Wang; Jiawei Li; Ziwei Yi; Zhenchi Zhao; Bin Guo; Huizheng Che; Xiaoye Zhang (Science of The Total Environment, 2023)

The mechanism of H2O in the superheated steam affecting the quality of in-situ pyrolysates of oil shale kerogen: Part B-favorable conversion of residues - Fumin Zhao; Bao Li; Daochang Che; Shengyu Liu (Fuel, 2023)

Microcystin-LR induced transgenerational effects of thyroid disruption in zebraﬁsh offspring by endoplasmic reticulum stress-mediated thyroglobulin accumulation and apoptosis - Weirong Si; Mengjie Zhao; Huimin Che; Zaiwei Wu; Yuchun Xiao; Xinxin Xie; Jiayao Duan; Tong Shen; Dexiang Xu; Sujuan Zhao (Environmental Pollution, 2023)

Decades of reforestation significantly change microbial necromass, glomalin, and their contributions to soil organic carbon - Mengling Zhang; Rongxiao Che; Zhibao Cheng; Hongkai Zhao; Chengwei Wu; Jinming Hu; Song Zhang; Dong Liu; Xiaoyong Cui; Yibo Wu (Agriculture, Ecosystems & Environment, 2023)

Assessment of toxic mechanisms and mode of action to three different levels of species for 14 antibiotics based on interspecies correlation, excess toxicity, and QSAR - Jin J. Li; Ya X. Yue; Jie F. Jiang; Sheng J. Shi; Hui X. Wu; Yuan H. Zhao; Fei F. Che (Chemosphere, 2023)

Study on the management efficiency of lanthanum/iron co-modified attapulgite on sediment phosphorus load - Yihe Qu; Li Zhao; Zhenghai Jin; Haoran Yang; Chengqi Tu; Feifei Che; Mohammad Russel; Xinshan Song; Wei Huang (Chemosphere, 2023)

Internal flow effect on the coupled CF and IL VIVs of a flexible marine riser subject to a uniform current - Guixin Zhao; Shuai Meng; Chidong Che; Shixiao Fu (Ocean Engineering, 2023)

Molecular mechanisms of plant adaptation to acid soils: A review - Jing CHE; Xue Qiang ZHAO; Ren Fang SHEN (Pedosphere, 2023)

Restrictions on Niobium enrichment by alteration of Niobium-rich biotite in pure water, acid, alkaline and fluoride-bearing solutions at 200 MPa and 300–600 °C - Zhao-Yu Yang; Ru-Cheng Wang; Xu-Dong Che; Daniel Harlov (Geochimica et Cosmochimica Acta, 2023)

Microcystin-leucine-arginine affects brain gene expression programs and behaviors of offspring through paternal epigenetic information - Jiayi Xu; Weiyun Zhang; Shengzheng Zhong; Xinxin Xie; Huimin Che; Weirong Si; Xun Tuo; Dexiang Xu; Sujuan Zhao (Science of The Total Environment, 2023)

The protective effect of Eleutheroside E against the mechanical barrier dysfunction triggered by lipopolysaccharide in IPEC-J2 cells - Huijuan Li; Rui Han; Feng Yong; Yueli Fan; Bao Zhao; Xiaocai Hu; Tianrui Zhang; Dongsheng Che (Research in Veterinary Science, 2023)

Modeling study on the roles of the deposition and transport of PM2.5 in air quality changes over central-eastern China - Lei Zhang; Jianjun He; Sunling Gong; Xiaomei Guo; Tianliang Zhao; Huizheng Che; Hong Wang; Chunhong Zhou; Jingyue Mo; Ke Gui; Yu Zheng; Lei Li; et al. (Journal of Environmental Sciences, 2023)

Bioinspired hierarchical delivery system with macrophage-like nanovesicles encapsulation for diabetic wound healing - Junyi Che; Xiangyi Wu; Yong Shi; Chuanhui Song; Yuanjin Zhao; Lingyun Sun (Chemical Engineering Journal, 2023)

Experimental study on the treatment of desulfurization wastewater from coal-fired power plant by spray evaporation - Zongkang Sun; Ning Zhao; Yongxin Feng; Fengjun Liu; Chenjian Cai; Guangmin Che; Yaping Zhang; Hao Wu; Linjun Yang (Environmental Science and Pollution Research, 2022)

Dual Drug Loaded pH-sensitive Micelles for Efficient Bacterial Infection Treatment - Yingxian Chen; Qian Zhao; Junhua Han; Xinmiao Lan; Jing Che; Meiwan Chen; Xing-Jie Liang; Xiaowei Ma (Pharmaceutical Research, 2022)

Effect of strontium on nutrient uptake, physiological parameters, and strontium localization in lettuce - Dong Yan; Kuke Ding; Yingxue He; Li Fan; Yongfei Che; Yingjun Zhao; Xiaoyan Jiang (Environmental Science and Pollution Research, 2022)

Pregnancy leads to changes in the brain functional network: a connectome analysis - Tongpeng Chu; Yuna Li; Kaili Che; Fanghui Dong; Heng Ma; Yinghong Shi; Peiyou Gong; Feng Zhao; Xicheng Song; Haizhu Xie; Ning Mao (Brain Imaging and Behavior, 2022)

Single-nucleotide polymorphisms responsible for pseudo-albinism and hypermelanosis in Japanese flounder (Paralichthys olivaceus) and reveal two genes related to malpigmentation - Bo Zhang; Kangkang Peng; Jinyuan Che; Na Zhao; Lei Jia; Dongkang Zhao; YaJuan Huang; YongGuan Liao; Xiaoxu He; Xiaoling Gong; Baolong Bao (Fish Physiology and Biochemistry, 2021)

Improvement of the CERES-Rice model using controlled experiments and a Meta-analysis - Qing Sun; Yanxia Zhao; Yi Zhang; Xianghong Che; Zaiqiang Yang; Yanling Song; Xiaohui Zheng (Theoretical and Applied Climatology, 2020)

Dynamic response characteristics and failure mode of slopes on the loess tableland using a shaking-table model test - Zhi-jian Wu; Duo-yin Zhao; Ai-lan Che; Da-wei Chen; Chao Liang (Landslides, 2020)

Tannic acid enhances the removal of chloroform from water using NaOH-activated persulfate - Xudong Zhao; Zhiguo Chen; Mingda Che; Sha Qiu; Renliang Huang; Wei Qi; Zhimin He; Rongxin Su (Environmental Chemistry Letters, 2020)

Effects of network topologies on stochastic resonance in feedforward neural network - Jia Zhao; Yingmei Qin; Yanqiu Che; Huangyanqiu Ran; Jingwen Li (Cognitive Neurodynamics, 2020)

The Effect of Abnormal Iron Metabolism on Osteoporosis - Jingmin Che; Jiancheng Yang; Bin Zhao; Ge Zhang; Luyao Wang; Songlin Peng; Peng Shang (Biological Trace Element Research, 2020)

The auxin‐inducible phosphate transporter AsPT5 mediates phosphate transport and is indispensable for arbuscule formation in Chinese milk vetch at moderately high phosphate supply - Xiaoning Fan; Xianrong Che; Wenzhen Lai; Sijia Wang; Wentao Hu; Hui Chen; Bin Zhao; Ming Tang; Xianan Xie (Environmental Microbiology, 2020)
Summary Phosphorus is a macronutrient that is essential for plant survival. Most land plants have evolved the ability to form a mutualistic symbiosis with arbuscular mycorrhizal (AM) fungi, which enhances phosphate (Pi) acquisition. Modulation of Pi transporter systems is the master strategy used by mycorrhizal plants to adapt to ambient Pi concentrations. However, the specific functions of PHOSPHATE TRANSPORTER 1 ( PHT1 ) genes, which are Pi transporters that are responsive to high Pi availability, are largely unknown. Here, we report that AsPT5, an Astragalus sinicus (Chinese milk vetch) member of the PHT1 gene family, is conserved across dicotyledons and is constitutively expressed in a broad range of tissues independently of Pi supply, but is remarkably induced by indole‐3‐acetic acid (auxin) treatment under moderately high Pi conditions. Subcellular localization experiments indicated that AsPT5 localizes to the plasma membrane of plant cells. Using reverse genetics, we showed that AsPT5 not only mediates Pi transport and remodels root system architecture but is also essential for arbuscule formation in A . sinicus under moderately high Pi concentrations. Overall, our study provides insight into the function of AsPT5 in Pi transport, AM development and the cross‐talk between Pi nutrition and auxin signalling in mycorrhizal plants.

Biochar shifts biomass and element allocation of legume-grass mixtures in Cd-contaminated soils - Yan Xiao; Leqi Wang; Zhuojun Zhao; Yeye Che (Environmental Science and Pollution Research, 2020)

Comparative Analysis of Nutrient Composition of Caulerpa lentillifera from Different Regions - Meijian Zhang; Yurong Ma; Xinyi Che; Zumei Huang; Peng Chen; Guanghua Xia; Meihui Zhao (Journal of Ocean University of China, 2020)

Synthesis and plant growth regulatory activities of 2′,3′-PhABA and iso-2′,3′-PhABA esters - Chuan Wan; Jiaqi Li; Fenghai Zhao; Dongyan Yang; Chuanliang Che; Shanshan Ding; Yimin Hu; Yumei Xiao; Zhaohai Qin (Molecular Diversity, 2020)

Upregulated Expression of CUX1 Correlates with Poor Prognosis in Glioma Patients: a Bioinformatic Analysis - Xiujie Wu; Fan Feng; Chuanchao Yang; Moxuan Zhang; Yanhao Cheng; Yayun Zhao; Yayu Wang; Fengyuan Che; Jian Zhang; Xueyuan Heng (Journal of Molecular Neuroscience, 2019)

α -Pyrone derivatives with cyto-protective activity from two Takla Makan desert soil derived actinomycete Nocardiopsis strains recovered in seawater based medium - Tingting Zhao; Yimin Chang; Tianjiao Zhu; Jing Li; Qianqun Gu; Dehai Li; Qian Che; Guojian Zhang (Natural Product Research, 2019)

Construction of rGO wrapping Cu2O/ZnO heterostructure photocatalyst for PNP and PAM degradation - Fang Liu; Yangli Che; Qingwen Chai; Mengfei Zhao; Yan Lv; Hui Sun; Yongqiang Wang; Juan Sun; Chaocheng Zhao (Environmental Science and Pollution Research, 2019)

Seminal Plasma Exosomes: Promising Biomarkers for Identification of Male and Pseudo-Males in Cynoglossus semilaevis - Bo Zhang; Na Zhao; Lei Jia; Kang Peng; Jinyuan Che; Kunming Li; Xiaoxu He; Jinsheng Sun; Baolong Bao (Marine Biotechnology, 2019)

Variation in MERRA-2 aerosol optical depth over the Yangtze River Delta from 1980 to 2016 - Enwei Sun; Huizheng Che; Xiaofeng Xu; Zhenzhu Wang; Chunsong Lu; Ke Gui; Hujia Zhao; Yu Zheng; Yaqiang Wang; Hong Wang; Tianze Sun; Yuanxin Liang; et al. (Theoretical and Applied Climatology, 2019)

Antibacterial and anticorrosive properties of CuZnO@RGO waterborne polyurethane coating in circulating cooling water - Guofei Jiang; Xufei Li; Yangli Che; Yan Lv; Fang Liu; Yongqiang Wang; Chaocheng Zhao; Xiaojuan Wang (Environmental Science and Pollution Research, 2019)

Identification of a major QTL on chromosome arm 2AL for reducing yellow rust severity from a Chinese wheat landrace with evidence for durable resistance - Zhen Wang; Junda Ren; Ziyi Du; Mingzhe Che; Yibin Zhang; Wei Quan; Xu Jiang; Yuan Ma; Yin Zhao; Zhongjun Zhang (Theoretical and Applied Genetics, 2019)

Detecting and attributing vegetation changes in Taihang Mountain, China - Shi Hu; Fei-yu Wang; Che-sheng Zhan; Ru-xin Zhao; Xiong-guo Mo; Liang-mei-zi Liu (Journal of Mountain Science, 2019)

Thioredoxin-interacting protein mediates mitochondrion-dependent apoptosis in early brain injury after subarachnoid hemorrhage - Yidan Liang; Xudong Che; Qing Zhao; Rami Darwazeh; Hongxia Zhang; Dengzhi Jiang; Jun Zhao; Xiang Xiang; Wang Qin; Liu Liu; Zhaohui He (Molecular and Cellular Biochemistry, 2019)

Natural variation ofCsSTOP1in tea plant (Camellia sinensis) related to aluminum tolerance - Hua Zhao; Wei Huang; Yange Zhang; Ziwei Zhang; Yong Li; Che Tang; Jie Huang; Dejiang Ni (Plant and Soil, 2018)

Vibrational resonance in a randomly connected neural network - Yingmei Qin; Chunxiao Han; Yanqiu Che; Jia Zhao (Cognitive Neurodynamics, 2018)

First report of tobacco mosaic virus infecting Benincasa hispida in Jiangxi Province in China - Feng Zhu; Yang Kai Zhou; Ya Qian Zhao; Yan Ping Che; Zhao Lin Ji (Journal of Plant Pathology, 2018)

First report of cucumber mosaic virus infecting Arachis hypogaea in Jiangxi Province in China - Feng Zhu; Yan Ping Che; Yang Kai Zhou; Shi Chang Cheng; Zheng Liu; Zhao Lin Ji (Journal of Plant Pathology, 2018)

Comparison of Two Air Pollution Episodes over Northeast China in Winter 2016/17 Using Ground-Based Lidar - Yanjun Ma; Hujia Zhao; Yunsheng Dong; Huizheng Che; Xiaoxiao Li; Ye Hong; Xiaolan Li; Hongbin Yang; Yuche Liu; Yangfeng Wang; Ningwei Liu; Cuiyan Sun (Journal of Meteorological Research, 2018)

Silicon accumulated in the shoots results in down-regulation of phosphorus transporter gene expression and decrease of phosphorus uptake in rice - An Yong Hu; Jing Che; Ji Feng Shao; Kengo Yokosho; Xue Qiang Zhao; Ren Fang Shen; Jian Feng Ma (Plant and Soil, 2018)

Comparison of Submicron Particles at a Rural and an Urban Site in the North China Plain during the December 2016 Heavy Pollution Episodes - Xiaojing Shen; Junying Sun; Xiaoye Zhang; Yangmei Zhang; Yaqiang Wang; Kaiyan Tan; Peng Wang; Lu Zhang; Xuefei Qi; Haochi Che; Zhouxiang Zhang; Junting Zhong; et al. (Journal of Meteorological Research, 2018)

Aerosol Hygroscopicity during the Haze Red-Alert Period in December 2016 at a Rural Site of the North China Plain - Xuefei Qi; Junying Sun; Lu Zhang; Xiaojing Shen; Xiaoye Zhang; Yangmei Zhang; Yaqiang Wang; Haochi Che; Zhouxiang Zhang; Junting Zhong; Kaiyan Tan; Huarong Zhao; et al. (Journal of Meteorological Research, 2018)

Optical and radiative properties of aerosols during a severe haze episode over the North China Plain in December 2016 - Yu Zheng; Huizheng Che; Leiku Yang; Jing Chen; Yaqiang Wang; Xiangao Xia; Hujia Zhao; Hong Wang; Deying Wang; Ke Gui; Linchang An; Tianze Sun; et al. (Journal of Meteorological Research, 2017)

Relative contributions of boundary-layer meteorological factors to the explosive growth of PM2.5 during the red-alert heavy pollution episodes in Beijing in December 2016 - Junting Zhong; Xiaoye Zhang; Yaqiang Wang; Junying Sun; Yangmei Zhang; Jizhi Wang; Kaiyan Tan; Xiaojing Shen; Haochi Che; Lu Zhang; Zhouxiang Zhang; Xuefei Qi; et al. (Journal of Meteorological Research, 2017)

Effect of Reducing Nitric Oxide in Rumex K-1 Leaves on the Photoprotection of Photosystem II Under High Temperature with Strong Light - Xingkai Che; Zishan Zhang; Liqiao Jin; Meijun Liu; Yuting Li; Huiyuan Gao; Shijie Zhao (Journal of Plant Growth Regulation, 2016)

Changing roles of ammonia-oxidizing bacteria and archaea in a continuously acidifying soil caused by over-fertilization with nitrogen - He Song; Zhao Che; Wenchao Cao; Ting Huang; Jingguo Wang; Zhaorong Dong (Environmental Science and Pollution Research, 2016)

The K+–Cl− Cotransporter KCC2 and Chloride Homeostasis: Potential Therapeutic Target in Acute Central Nervous System Injury - Haijian Wu; Xiaoru Che; Junjia Tang; Feiqiang Ma; Kun Pan; Mingfei Zhao; Anwen Shao; Qun Wu; Jianmin Zhang; Yuan Hong (Molecular Neurobiology, 2016)

Double-Edged Roles of Nitric Oxide Signaling on APP Processing and Amyloid-β Production In Vitro: Preliminary Evidence from Sodium Nitroprusside - Zheng-Xu Cai; Hui-Shu Guo; Che Wang; Min Wei; Cheng Cheng; Zhao-Fei Yang; Yin-Wang Chen; Wei-Dong Le; Song Li (Neurotoxicity Research, 2016)

Functional analysis of β-amyrin synthase gene in ginsenoside biosynthesis by RNA interference - Che Zhao; Tianhui Xu; Yanlong Liang; Shoujing Zhao; Luquan Ren; Qian Wang; Bo Dou (Plant Cell Reports, 2015)

Oxidative stress, apoptosis, and cell cycle arrest are induced in primary fetal alveolar type II epithelial cells exposed to fine particulate matter from cooking oil fumes - Ying Liu; Yan-Yan Chen; Ji-Yu Cao; Fang-Biao Tao; Xiao-Xia Zhu; Ci-Jiang Yao; Dao-Jun Chen; Zhen Che; Qi-Hong Zhao; Long-Ping Wen (Environmental Science and Pollution Research, 2015)

Analyses of aerosol optical properties and direct radiative forcing over urban and industrial regions in Northeast China - Huizheng Che; Hujia Zhao; Yunfei Wu; Xiangao Xia; Jun Zhu; Hong Wang; Yaqiang Wang; Junying Sun; Jie Yu; Xiaoye Zhang; Guangyu Shi (Meteorology and Atmospheric Physics, 2015)

Actinopolyspora dayingensis sp. nov., a novel halophilic actinomycete isolated from a hypersaline lake - Tong-Wei Guan; Hui-Ping Zhao; Zhen-Ming Che; Xiao-Ping Zhang; Li-Li Zhang (Antonie van Leeuwenhoek, 2013)

Cloning, expression and characterization of squalene synthase from Inonotus obliquus - Fangliang Zheng; Nan Liu; Yuchen Che; Li Zhang; Lijie Shao; Junfeng Zhu; Jian Zhao; Haixin Ai; Alan K. Chang; Hongsheng Liu (Genes & Genomics, 2013)

Geological events play a larger role than P leistocene climatic fluctuations in driving the genetic structure of Q uasipaa boulengeri ( A nura: D icroglossidae) - Fang Yan; Weiwei Zhou; Haitao Zhao; Zhiyong Yuan; Yunyu Wang; Ke Jiang; Jieqiong Jin; Robert W. Murphy; Jing Che; Yaping Zhang (Molecular Ecology, 2013)
Paleoclimatic and paleogeological events have been identified as being the two main drivers of genetic structuring in extant organisms. We used a montane stream‐dwelling frog, Q uasipaa boulengeri , to explore the relative roles played by these drivers on species in southern C hina, a region needing thorough studies. We detected four major matrilines, and no broadly distributed haplotypes occurred. The complex orogenesis of south‐western China drove matrilineal divergence in Q . boulengeri into highly structured geographical units. These matrilines subsequently persisted in situ with stable populations rather than undergoing expansions during glacial cycling. The unification of the upper and middle Y angtze R iver in the Three Gorges mountain region mediated downstream colonization of this frog. Analyses identified geological events as playing a larger role than climatic fluctuations in driving the population history of Q . boulengeri . Nuclear allele analyses indicated gene flow; this maintained genetic cohesion of the species. S outh‐eastern S ichuan B asin was identified as the area of secondary contact for several matrilines, and this area deserves further study and special protection.

Erratum to: The Toxicological Effects in Brain of Mice Following Exposure to Cerium Chloride - Haiquan Zhao; Zhe Cheng; Jie Cheng; Renping Hu; Yi Che; Yaling Cui; Ling Wang; Fashui Hong (Biological Trace Element Research, 2012)

Assessment of the modulating effects of fructo-oligosaccharides on fecal microbiota using human flora–associated piglets - Jian Shen; Baorang Zhang; Hua Wei; Chuanyan Che; Dezhong Ding; Xiuguo Hua; Peter Bucheli; Linghua Wang; Yixue Li; Xiaoyan Pang; Liping Zhao (Archives of Microbiology, 2010)

Aerosol optical properties and its radiative forcing over Yulin, China in 2001 and 2002 - Huizheng Che; Xiaoye Zhang; Stephane Alfraro; Bernadette Chatenet; Laurent Gomes; Jianqi Zhao (Advances in Atmospheric Sciences, 2009)

Analysis of sky conditions using 40 year records of solar radiation data in China - H. Z. Che; G. Y. Shi; X. Y. Zhang; J. Q. Zhao; Y. Li (Theoretical and Applied Climatology, 2007)

Postnatal expression and denervation induced up-regulation of aquaporin-5 protein in rat sweat gland - Lei Ma; Yuan-Gui Huang; Hua He; Yan-Chun Deng; Hai-Feng Zhang; Hong-Lei Che; Ji-Yu Tian; Gang Zhao (Cell and Tissue Research, 2007)

Approximations of the scattering phase functions of particles - Jian-Qi Zhao; Guangyu Shi; Huizheng Che; Guangguang Cheng (Advances in Atmospheric Sciences, 2006)